2017
DOI: 10.1136/sextrans-2017-053126
|View full text |Cite
|
Sign up to set email alerts
|

Extra-rectal lymphogranuloma venereum in France: a clinical and molecular study

Abstract: In the span of 6 years, 56 extrarectal LGV cases were confirmed through genotyping in France. Extrarectal LGV seemed to share a common epidemiological background with rectal disease in terms of affected population and genovar distribution. HIV prevalence was lower than expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
1
9
0
1
Order By: Relevance
“…Lymphogranuloma venereum (LGV) is endemic among European men who have sex with men (MSM) since 2003 . It is a relatively common cause of proctitis, but rarely causes genital or oro‐pharyngeal infections . Although other strains like serovar/genovar L2 have been identified, subvariant L2b is the causative strain in the majority of cases in Europe, and a high degree of clonal relatedness has been found with genome sequencing techniques .…”
Section: Epidemiologymentioning
confidence: 99%
“…Lymphogranuloma venereum (LGV) is endemic among European men who have sex with men (MSM) since 2003 . It is a relatively common cause of proctitis, but rarely causes genital or oro‐pharyngeal infections . Although other strains like serovar/genovar L2 have been identified, subvariant L2b is the causative strain in the majority of cases in Europe, and a high degree of clonal relatedness has been found with genome sequencing techniques .…”
Section: Epidemiologymentioning
confidence: 99%
“…The last case was published in a retrospective revision of 56 cases of extrarectal LGV. One of six patients with pharyngeal infection showed an ulcer on the tongue and a cervical lymphadenopathy 7. He was diagnosed by NAAT and presumably treated with doxycycline for 21 days (data not specified).…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, the diagnosis of LGV genital lesions is made late after the onset of symptoms, due to lack of suspicion. 3 Recent European case series showed that, in contrast to proctitis, 50% or less of patients with LGV genital ulcers were HIV-positive. 3 The differential diagnosis of a genital ulcer should include syphilis, herpes virus, chancroid,…”
Section: Casementioning
confidence: 99%
“…2 However, most HE cases are aetiologically categorized as irritant contact dermatitis (ICD), 10-20% as allergic contact dermatitis (ACD) and very few as protein contact dermatitis (PCD). [3][4][5] Individuals with AD are thought to have an increased risk of ICD, as explained by reduced threshold to irritants.…”
Section: Casementioning
confidence: 99%